Kajian Hukum dan Etika Kesehatan terhadap Tanggung Jawab Tenaga Medis di Fasilitas Pelayanan Publik - Rinna Dwi Lestari (RETORIKA: Journal of Law, Social, and Humanities, 2025)
This study aims to: 1) analyze the regulation of medical personnel's responsibilities in public service facilities from a legal and health ethics perspective, and 2) assess the standards and limits of accountability in the provision of services to patients. This is a normative legal study using statutory, conceptual, and historical approaches. The legal materials analyzed include regulations regarding medical practice, health personnel, health services, consent for medical procedures, patient safety, and medical records, as well as academic literature, supporting documents, and related scientific studies. The analysis is conducted through legal interpretation, legal theory, and legal principles to assess the conformity of medical actions with legal provisions and professional ethics. The results of the study indicate, first, that the responsibility of medical personnel is determined by compliance with professional standards, operational procedures, and the fulfillment of patient rights, including consent for medical procedures. Second, this regulation creates a balance between patient protection and legal certainty for medical personnel in the provision of public health services, so that inherent medical risks do not automatically give rise to liability as long as actions are carried out in accordance with applicable legal and ethical norms.